Changes in urine volume and serum albumin in incident hemodialysis patients. Issue 4 (25th November 2016) - Eriguchi, Rieko; Obi, Yoshitsugu; Rhee, Connie M.; Chou, Jason A.; Tortorici, Amanda R.; Mathew, Anna T.; Kim, Taehee; Soohoo, Melissa; Streja, Elani; Kovesdy, Csaba P.; Kalantar‐Zadeh, Kamyar
Abstract: Introduction: Hypoalbuminemia is a predictor of poor outcomes in dialysis patients. Among hemodialysis patients, there has not been prior study of whether residual kidney function or decline over time impacts serum albumin levels. We hypothesized that a decline in residual kidney function is associated with an increase in serum albumin levels among incident hemodialysis patients. Methods: In a large national cohort of 38, 504 patients who initiated hemodialysis during 1/2007‐12/2011, we examined the association of residual kidney function, ascertained by urine volume and renal urea clearance, with changes in serum albumin over five years across strata of baseline residual kidney function, race, and diabetes using case‐mix adjusted linear mixed effects models. Findings: Serum albumin levels increased over time. At baseline, patients with greater urine volume had higher serum albumin levels: 3.44 ± 0.48, 3.50 ± 0.46, 3.57 ± 0.44, 3.59 ± 0.45, and 3.65 ± 0.46 g/dL for urine volume groups of <300, 300–<600, 600–<900, 900–<1, 200, and ≥1, 200 mL/day, respectively (Ptrend < 0.001). Over time, urine volume and renal urea clearance declined and serum albumin levels rose, while the baseline differences in serum albumin persisted across groups of urinary volume. In addition, the rate of decline in residual kidney function was not associated with the rate of change in albumin. Discussion: Hypoalbuminemia in hemodialysis patients is associated with lower residual kidney function. Among incident hemodialysis patients, there is a gradual rise in serum albumin that is independent of the rate of decline in residual kidney function, suggesting that preservation of residual kidney function does not have a deleterious impact on serum albumin levels.